2017
DOI: 10.1038/srep46161
|View full text |Cite
|
Sign up to set email alerts
|

Acidic pH environment induces autophagy in osteoblasts

Abstract: Osteoblasts (OBs) play an important role in bone fracture healing, yet the extreme adverse microenvironment in fracture sites has a negative impact on the survival of OBs. Therefore, it is important to study how OBs behave in the complex fracture microenvironment. Studies have shown that autophagy plays a pivotal role in maintaining cellular homeostasis and defending the cell against adverse microenvironments. In this study we found the induction of autophagy in OBs at femoral bone fracture sites, which may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 46 publications
(53 reference statements)
0
37
0
Order By: Relevance
“…Such acidic microenvironments induce malignant progression [6]. It has been shown that acidic pH promotes local invasive growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such acidic microenvironments induce malignant progression [6]. It has been shown that acidic pH promotes local invasive growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The fixed cells were treated with 5% BSA for 30 min and stained with DAPI for 6 min, after which the coverslips were air-dried and mounted in Gel Tol. mRFP-GFP-LC3 fluorescence was observed under a fluorescence microscope, as previously described [6,21,22]. We counted the numbers of mRFP-GFP-LC3 punctae in three independent visual fields.…”
Section: Detection Of Mrfp-gfp-lc3mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, considering that we measured the BMP-2 release in physiological conditions, and that we left the samples on the bench to analyze the release of factors at T0, T7, and T14 without adding any substances, apart from EDTA, this could explain the low production of BMP-2 observed in our study. However, since the development of an acidic tissue environment is common in wound healing sites [37], the use of the liquid fibrinogen, for instance at implant sites, may enhance the repair processes as the low pH contributes to stimulate the release of BMP-2. During bone healing, the pH becomes neutral and finally alkaline, thus stimulating alkaline phosphatase and osteocalcin [36].…”
Section: Discussionmentioning
confidence: 99%
“…The acidic pH of lysosomes maintained by the vacuolar-type H+-ATPase (v-ATPase) [2] that pumps protons from the cytoplasm into the lysosomal lumen was to keep the activity of ~ 60 types of hydrolytic enzymes [3]. Moreover, recent literature reports revealed that acidic pH of lysosomes are closely related to the autophagy [4], so that well known of the precise lysosomes pH changes will give more information on the autophagy process and status. Based on our studies and literature review, amine positive charged nanoparticle endocytosis will probably increase the pH change in endo/lysosomes, such as primary and secondary amine PEG decorated nanoparticles or some hydrophilic decoration on the particle surface [5,6].…”
Section: Introductionmentioning
confidence: 99%